Knowledge Management of Cultural Event Components to Promote Community Tourism at Talad Noi in Bangkok - Nunthasiriphon, Sumalee; Khrouthongkhie, Nuaon; Ngamsukasemsri, Thidarat (Journal of Management Science Nakhonratchasima University, 2025)
This study integrated both qualitative and quantitative research methodologies. It aimed to investigate the cultural context of the Talad Noi community in Bangkok. It also analyzed the potential of components of cultural event organization. The objective was to propose a knowledge management framework for organizing cultural events that promote community-based tourism. The qualitative data were analyzed using content analysis. Quantitative data from a questionnaire completed by 400 Thai tourists were examined using percentages, means, and standard deviations. The findings revealed that: 1) four categories of cultural context: physical culture, intangible culture, traditional crafts and occupations, and culinary traditions. 2) Twelve types of cultural activities were identified, including Chinese snack-making, traditional cooking, ritual practices, embroidery, beadwork, blacksmithing, local museum tours, architectural appreciation, café tours, art experiences, storytelling through images, and check-in spots. 3) Most tourists were male, aged 18-27, held a bachelor’s degree, and were students. 4) The study also highlighted three key components of cultural activity organization: (1) tourism resources with high potential in terms of facilities and activities, followed by accommodation and attractions, and (2) support for activity organization, with atmosphere creation being the most desired, followed by media usage and venue layout planning. Based on these findings, a five-step knowledge management approach was proposed to promote the sustainable preservation of community culture: (1) data collection, (2) activity design, (3) community engagement, (4) brand development, and (5) information communications.